Oceanside dwelling for Mrs. Clinton Walker, sheet 1, plot plan - Frank Lloyd Wight:::::::::
Plot plan which Mills traced from Frank Lloyd Wright's original design for the Walker residence, with additions contributed by Mills for his project on the residence.